Reframing performance's ontology: hybridity in contemporary performance art's ontology. Issue 3 (2nd September 2022) - Willard, Zane Austin
ABSTRACT: I argue performance studies' modernist ontological assumptions of fleeting are antithetical to contemporary performance art which relies on digital technology for mediated viewing processes. In this essay, I argue for a hybrid postmodern performance studies that allow for varying modes of experiencing performance art. I situate Allan Kaprow and Fluxus as the genealogical beginning of performance and argue that Peggy Phelan's ontological assumptions of performance are inherently modernist. I then pose a postmodern approach to performance studies that embrace an embodiment of hybrid viewing methodologies of performance. Lastly, I use three examples as embodiments and symptomatic representations of this embodiment of a hybrid postmodern performance ontology.